Great expectations and the end of the Depression - Gauti B. Eggertsson (Federal Reserve Bank of New York, 2005)
This paper argues that the U.S. economy's recovery from the Great Depression was driven by a shift in expectations brought about by the policy actions of President Franklin Delano Roosevelt. On the monetary policy side, Roosevelt abolished the gold standard and—even more important—announced the policy objective of inflating the price level to pre-depression levels. On the fiscal policy side, Roosevelt expanded real and deficit spending. Together, these actions made his policy objective credible; they violated prevailing policy dogmas and introduced a policy regime change such as that described in work by Sargent and by Temin and Wigmore. The economic consequences of Roosevelt's policies are evaluated in a dynamic stochastic general equilibrium model with sticky prices and rational expectations.
Keywords: E52; E63; 330; deflation; Great Depression; regime change; zero interest rates; Geldpolitik; Finanzpolitik; Diskretionäre Politik; Neukeynesianische Makroökonomik; Dynamisches Gleichgewicht; Mikroökonomische Fundierung; USA